Algorithm to choose the appropriate test for comparison between two groups - Sampada B Dessai (Cancer Research, Statistics, and Treatment, 2021)
The current manuscript describes the method of selection of statistical tests for comparing two groups. In this article, we discuss the factors on which the selection of tests depends and provide an algorithm for the selection of the inferential statistical test.